2005
DOI: 10.1097/01.mpa.0000168227.74203.e4
|View full text |Cite
|
Sign up to set email alerts
|

Serum Paraoxonase (a High-density Lipoprotein-associated Lipophilic Antioxidant) Activity and Lipid Profile in Experimental Acute Pancreatitis

Abstract: Our results suggest that an abnormal lipid profile and decreased PON1 activity may have a role in the pathogenesis of acute pancreatitis in which HDL-associated antioxidant defense is impaired.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
23
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 13 publications
5
23
0
Order By: Relevance
“…In this regard, free radicals and oxidative stress have been implicated in the pathogenesis of acute pancreatitis and have been shown to correlate with the severity of pancreatitis [30,31]. Consistent with previous reports on critically ill patients [32-34], we showed that the levels of HDL and APO A-I at admission to ICU were significantly lower in non-survivors.…”
Section: Discussionsupporting
confidence: 92%
“…In this regard, free radicals and oxidative stress have been implicated in the pathogenesis of acute pancreatitis and have been shown to correlate with the severity of pancreatitis [30,31]. Consistent with previous reports on critically ill patients [32-34], we showed that the levels of HDL and APO A-I at admission to ICU were significantly lower in non-survivors.…”
Section: Discussionsupporting
confidence: 92%
“…Jung et al [36] reported that plasma viscosity mainly depends on plasma fibrinogen, albumin, globulin, and lipids levels. It has also been shown that cholesterol levels were increased in alcohol-induced acute pancreatitis [4]. Hematocrit and erythrocyte count determine the viscosity of whole blood.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported in an animal study that the mortality from alcohol-induced pancreatitis was caused by a transient increase of pancreatic amylase output and plasma cholecystokinin (CCK) levels [2]. As ethanol is initially metabolized by the microsomal ethanol oxidizing system, creating an oxidative environment, oxidative stress appears to be the initial factor in the pathogenesis of alcoholic pancreatitis [1][2][3][4]. However, the detailed mechanism of induction of alcoholic pancreatitis is still not well understood.…”
Section: Introductionmentioning
confidence: 97%
“…16 In this sense, a recent study focusing on acute pancreatitis has reported that PON1 activity and HDL level were lower in acute pancreatitis, whereas the mean levels of total cholesterol, low-density lipoproteins, and malonyldialdehyde were significantly higher. 17 A decrease in PON1 activity could be related with changes in liver expression, but also with the increase in oxidative stress. As what occurs with other antioxidant enzymes, such as superoxide dismutase, the inhibitory action of PON1 has been shown to be associated to an inactivation reaction that results in the lost of the functional active sites in the enzyme.…”
Section: Introductionmentioning
confidence: 98%